Equality of arms, impartiality of the judiciary and the role of the parties in the pre-trial inquiry: the perspective of Italian criminal justice - Stefano Ruggeri (Revista Brasileira de Direito Processual Penal, 2018)
The analysis of the prosecutorial inquiry in Italian criminal proceedings displays a complex scenario. In spite of the progressive enhancement of participatory rights of private parties, the overwhelming role of the investigative authorities does not set the necessary conditions for effective equality of arms, while largely frustrating the tasks of the judiciary. To a great extent, the maintenance of several decision-making and coercive powers of the public prosecutor still largely reflect the old conception of an independent body of justice. Even though the individuals involved in the prosecutorial inquiry are ensured participation in a number of police and prosecutorial investigations, legal assistance often lacks effectiveness, and the possibilities of defence lawyers conducting autonomous investigations are scant and only achieve a formal level of par condicio. Certainly, this set-up cannot be justified in a human rights-oriented model of criminal justice. De lege ferenda, the enhancement of the tasks of competent judge for the pre-trial inquiry, who under Italian law is not an investigative magistrate but is called upon to ensure the proper fulfilment of procedural safeguards, appears to constitute today the best alternative to one-sided investigations and the dominant role of the investigative authorities.